Particulate Nature of Acid Phosphatase Released from Thrombocytes - Polášek, J (Thrombosis and Haemostasis, 1968)
Acid phosphatases are released from thrombocytes into serum during coagulation of native PRP or blood in particulate form. Latent activity probably masked in phospholipoprotein structures could be discovered with the use of detergent.Some physicochemical properties are described with regard to the PF 3 like activity of serum.Possible connection to platelet lysosomes is discussed.